2019
DOI: 10.1071/rd18403
|View full text |Cite
|
Sign up to set email alerts
|

Paternal exposure to bupropion affects postnatal development in the offspring

Abstract: The aim of this study was to evaluate whether paternal exposure to bupropion hydrochloride (BUP), an inhibitor of dopamine and noradrenaline reuptake, would affect the postnatal development of offspring. Male mice were divided into a BUP-treated (40mgkg−1day−1 by gavage, 45 days) or control (saline by gavage, 45 days) group (n=20 in each group). From Day 35 to Day 45 of treatment, males were allowed to mate with drug-naïve female mice. Postnatal development of the offspring (both sexes) was evaluated from Post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
1
1
Order By: Relevance
“…The current findings showed that paternal exposure to FNT did not cause any changes in the developmental landmarks among all progeny groups. These results are contradictory to a previous study, which found that bupropion hydrochloride (BUP) administration decreased AGD in both male and female rats [ 62 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The current findings showed that paternal exposure to FNT did not cause any changes in the developmental landmarks among all progeny groups. These results are contradictory to a previous study, which found that bupropion hydrochloride (BUP) administration decreased AGD in both male and female rats [ 62 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The physical and behavioral parameters were assessed in one male pup and one female pup from each litter ( n = 10 per group), and the mean number of days required for the appearance of each of the parameters was calculated as previously described (Carvalho et al, 2016). The physical parameter included pinna unfolding, incisor eruption, and eye opening (Sanches et al, 2019). The following behavioral reflexes were also assessed: righting reflex (the pups ware placed in the dorsal decubitus over a flat surface and observed the age that each pup returns from the prone position) (Anjos et al, 2022), negative geotaxis (pups were kept on a 45° inclined plane face‐down and observed the age that each pup was able to rotate at least 135°) (Ruhela et al, 2019), palmar grasp reflex (light pressure with a paper clip was applied until the pup showed a palmar grasp with the forepaw) (Laliberte et al, 2021), auditory startle (body retraction, with a transitory immobility in response to a sound stimulus) (Fragoso et al, 2017), and vibrissae placing (pup held by tail with head facing edge of bench with vibrissae just touching vertical surface and observed the lifting of the head and the extension of the forepaws in a direction of the bench) (Smart & Dobbing, 1971).…”
Section: Methodsmentioning
confidence: 99%